Metode Total Physical Responses dalam Pengoptimalan Bahasa Reseptif Siswa Sekolah Dasar - Bintun Saniyatus Salamah; Fida Anggi Agustin; Nadiah Farah Habibah; Muhammad Nofan Zulfahmi (Lembaga Pengembangan Kinerja Dosen, 2025)
TPR is a learning method that combines physical movements with verbal instructions to improve students' understanding of the language they hear. The aim of this research is to determine the application of the Total Physical Response (TPR) method to optimize students' receptive language abilities. This research investigates how TPR can improve students' ability to listen and respond to verbal instructions. Research shows that using TPR improves vocabulary comprehension, speeds responses to commands, and optimizes overall receptive language skills. Apart from that, TPR has also proven to be effective in creating a fun and interactive learning atmosphere, thus further motivating students to learn languages. This makes TPR an effective way to develop students' receptive language skills more comprehensively.